(untitled) (Journal of Applied Learning and Teaching, 2024)
We designed and developed a virtual reality game, MemoryTrail VR, to learn about brain anatomy and the nervous system using a serious games design and assessment framework with a focus on purpose that was reflected in five elements: content, fiction and narrative, mechanics, aesthetics and graphics, and framing. We added a sixth element, motivation and memory, with the aim to bridge the gap between student engagement and the content being taught and, in doing so, aid in the retention of knowledge. This was executed through the introduction of knowledge interweaved in a storyline that was relatable to our undergraduate students from a local university in Singapore. The 21-item questionnaire data validated that MemoryTrail VR was a serious game designed with components which were mainly coherent and cohesive with its purpose. We found that using a structured framework to design and evaluate the game enabled us to collate meaningful feedback and identify specific areas for improvement for the next version of the game with the goal of eventually developing a serious game that is theory- and evidence-driven. There was a significant increase in the percentage of students who answered conceptual questions correctly when comparing the pre- and in-game quizzes, providing evidence of learning achieved by the students because of the gameplay.